2010
DOI: 10.1542/neo.11-8-e419
|View full text |Cite
|
Sign up to set email alerts
|

Infection Control Practices in the NICU: What is Evidence-based?

Abstract: has disclosed that she is a member of the speakers' bureau for Sanofi Pasteur. This commentary does not contain a discussion of an unapproved/ investigative use of a commercial product/device. AbstractNosocomial infections cause significant morbidity and mortality in neonatal intensive care unit (NICU) patients. Neonates, particularly those who are preterm and low birthweight, are at higher risk of acquiring infections compared with term and older infants. As a result, many interventions have been established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…Gloves are commonly worn with the intent to reduce the transmission of infection among hospitalized patients and between healthcare providers and patients; however, hand contamination can occur even when gloves are worn during patient care 11. Hand hygiene remains the most effective, evidence-based measure for preventing infection in the NICU12; however, researchers have found that hand hygiene compliance among healthcare providers is low when gloves are worn 10,15. Despite high rates of self-reported compliance with hand hygiene practices,15 healthcare providers' observed compliance is typically much lower 11,15.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gloves are commonly worn with the intent to reduce the transmission of infection among hospitalized patients and between healthcare providers and patients; however, hand contamination can occur even when gloves are worn during patient care 11. Hand hygiene remains the most effective, evidence-based measure for preventing infection in the NICU12; however, researchers have found that hand hygiene compliance among healthcare providers is low when gloves are worn 10,15. Despite high rates of self-reported compliance with hand hygiene practices,15 healthcare providers' observed compliance is typically much lower 11,15.…”
Section: Discussionmentioning
confidence: 99%
“…These institutions are enforcing universal gloving practices with all NICU patient contact. 12 However, in their drafted recommendations for infection control in the NICU, the Healthcare Infection Control Practices Advisory Committee of the Centers for Disease Control and Prevention (CDC) currently offers no recommendation for universal gloving to prevent the spread of infection. 13 The Advisory Committee points to the lack of high-quality evidence associating universal gloving practices with decreased rates of neonatal infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hand washing, isolation, surveillance, seasonal screening of visitors for potential infection, and validating the immunization status of the sibling visitors may be challenging. 23 Nurses must advocate for premature infants to ensure patient safety and prevent infection that can lead to long-term sequelae. 2 …”
Section: Prevention Of Infectionmentioning
confidence: 99%